1975
DOI: 10.1073/pnas.72.6.2251
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond detection of an intermediate in the photochemical reaction of bacterial photosynthesis.

Abstract: Analysis of the spectrum suggests that the formation of pF involves electron transfer from one bacteriochlorophyll molecule to another within the reaction center, or possibly from bacteriochlorophyll to the bacteriopheophytin of the complex. The initial absorbance changes after flash excitation also include a bleaching of an absorption band at 800 nm. The bleaching decays with T AZ 30 psec. The bleaching appears not to be a secondary effect, but rather to reveal another early step in the primary photochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
84
2

Year Published

1976
1976
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(94 citation statements)
references
References 14 publications
8
84
2
Order By: Relevance
“…Evidence for the intermediate comes from picosecond spectroscopy, whichhas suggested that although the (BChl)2 is oxidized within 10 ps of a flash of light [1 ], the primary acceptor is not reduced until some 100-200 ps later [2,3]. During this interval the electron is proposed to reside on the low redox potential I, as part of a transient [(BChl)2÷'I-'] state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for the intermediate comes from picosecond spectroscopy, whichhas suggested that although the (BChl)2 is oxidized within 10 ps of a flash of light [1 ], the primary acceptor is not reduced until some 100-200 ps later [2,3]. During this interval the electron is proposed to reside on the low redox potential I, as part of a transient [(BChl)2÷'I-'] state.…”
Section: Introductionmentioning
confidence: 99%
“…During this interval the electron is proposed to reside on the low redox potential I, as part of a transient [(BChl)2÷'I-'] state. If normal forward photochemistry is to occur, this state reduces X in 100-200 ps [2,3] but if this is blocked by the prior chemical reduction [4] or removal [5] of X, the transient state has a lifetime of nanoseconds before decaying (t½ ~, 10 ns at 300°K; "~ 30 ns at 80°K [4,6]). It has been suggested [7] that [-" has some spectrophotomeric characteristics of reduced bacteriopheophytin (BPh-").…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern has been observed for the DeVault-Chance ET process between cytochrome and the reaction centre in chromatium [ 51. Experimental studies of the primary charge separation steps in bacterial photosynthesis [6,7] have established that several of the elementary ET processes are temperature independent over a wide temperature range [8]. The ET process between bacteriopheophtin (BPh) and ubiquionone-10 (Q) [ 6-81:…”
Section: Introductionmentioning
confidence: 99%
“…It is my belief that these agonies were counterproductive in the extreme. (33,8). From there it is handed within a fraction of a nanosecond still further to the so-called primary acceptor, now believed in the case of photosynthetic bacteria to be a complex of a nonheme iron and a quinone (31).…”
mentioning
confidence: 99%